Proposal of Criteria to prioritize the inspection of multiple-use dams in light of the National Dam Safety Policy (PNSB) (Research, Society and Development, 2025)
The Brazilian National Dam Safety Policy (PNSB), established by Law No. 12,334/2010, set out guidelines for dam risk management. However, its implementation faces challenges, particularly regarding multipurpose dams under state jurisdiction, which are often small, lack mandatory technical documentation, and are overseen by agencies with limited resources. This study proposes objective and operational criteria to support the prioritization of inspections. The methodology included a literature and regulatory review covering federal and state legislation, ANA documents, technical literature, and previous screening models. Based on this, a prioritization matrix with four binary criteria was developed: (a) downstream population or infrastructure; (b) visibly medium or large size; (c) visible signs of structural issues; and (d) absence of formal regularization. The presence of three or more criteria indicates high inspection priority. The matrix was tested in a case study of four dams registered with IGAM, using public and georeferenced data. Results showed its technical feasibility, even without on-site inspection, by using remote sensing. A standardized dam size classification, based on height and reservoir volume, was also proposed. Many small dams showed high downstream exposure. The study concludes that simple, verifiable criteria enable strategic risk screening, resource optimization, and disaster prevention. The method is a preliminary risk management tool, not a replacement for in-depth technical analysis. Further sample expansion and criteria refinement are recommended.